A latent transition analysis of longitudinal stability of peer victimization experiences among Chinese adolescents. (April 2022) - Ye, Zhi; Harrison, Sayward E.; Lin, Danhua
Abstract: Background: Peer victimization is a source of stress for many adolescents and has important implications for their psychosocial development. Importantly, adolescents' experiences of peer victimization are dynamic and may change over time, due to individual and school-based contextual factors. Objective: The goal of the current study was to examine the stability of peer victimization and predictive effects of individual and contextual factors on the changes in patterns of victimization for Chinese adolescents over a 12-month period. Participants and setting: A total of 1281 Chinese middle school students (Time 1 [T1]: Mage = 13.40, SD = 0.97; 56.3% males) participated in the study. Methods: Adolescents self-reported on a variety of variables at baseline (i.e., T1) and 12 months later (i.e., Time 2 [T2]). Latent Profile Analysis (LPA) and Latent Transition Analysis (LTA) were used to identify latent profiles and transition patterns of victimization among adolescents. Additionally, logistic regressions were used to investigate the effects of social emotional competence and school climate on the victimization types and transition patterns of adolescents. Results: Adolescents' patterns of victimization could be divided into three groups, including (1) a low victimized group, (2) a moderately and verbally victimized group, and (3) a severe multi-type victimized group. Adolescents in the low victimized group showed the highest stability in their peer victimization experiences from T1 to T2. Social emotional competence and school climate had significant effects on the probability of transitioning from the low victimization group to a higher victimization group over time. Conclusions: These findings emphasize the importance of early intervention efforts designed to curb peer victimization among Chinese adolescents.